Fuzzy approach to forecasting the dynamics ofvegetation indices - Aliyev, E.R.; Salmanov, F.M. (Проблемы управления и информатики, 2022)
Modern satellite monitoring technologies provide agricultural producers with valuable information on the health status of crops. The ability of remote sensors to detect slight variations in vegetation makes them a useful tool for quantitatively assessing variability within a given field, evaluating crop growth, and managing land based on current conditions. Remote sensing data, collected on a regular basis, allow producers and agronomists to create up-to-date vegetation maps reflecting the health and vigor of crops, analyze changes in plant condition over time, and forecast yield for a specific planting area. Сучасні технології супутникового моніторингу поверхні Землі надають сільськогосподарським виробникам корисну інформацію — стан здоровʼя посівних культур. Здатність віддаленого датчика виявляти незначні відмінності у рослинності робить його корисним інструментом для кількісної оцінки мінливості в межах заданого поля, оцінки зростання сільськогосподарських культур та управління угіддями на основі поточних умов. Дані дистанційного зондування, що збираються на регулярній основі, дозволяють виробникам та агрономам складати поточну карту вегетації, що відображає стан та силу посівних культур, аналізувати динаміку зміни у стані рослин, а також прогнозувати врожайність на конкретній посівній площі.